Performance Analysis of Inverter Fed Single Phase Induction Motor Drive - Diyoke, Gerald Chidozie; Eya, Candidus Ugwuoke; Obi, Patrick Ifeanyichukwu; Onwuka, Ifeanyichukwu Kalu (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
This paper presents performance analysis of effects of modulation index on cascaded multilevel inverter fed single phase induction motor drive using closest level control technique. The modulation index is varied to analyze its performance. The effects on inverter output voltage, current, induction motor speed, electromagnetic torque and total harmonic distortion (THD) are considered. Both the load torque and modulation index are varied to determine the motor performance. The Closest (Nearest) control method is applied for generating firing pulses for the cascaded multilevel inverter power switches. By the application of this method, the switching losses are greatly mitigated when compared with high switching frequency of Pulse Width Modulation (PWM) schemes. MATLAB/SIMULINK software is used to obtain the system simulation results. The performance evaluation of this work was targeted on the modulation index range from 0.7 to 1.2 and for selected load torque values of 0 Nm, 2 Nm and 4 Nm. It is observed that modulation index affects the motor performance. When modulation index is 1.0 under different load torques, 6.2 % - 6.7 % range of voltage THD was obtained. When the modulation index becomes 1.2, motor speed and electromagnetic torque resulted to 1327 RPM and 20 Nm respectively with stability time of 0.7 sec under load torque of 4 Nm.